2022
DOI: 10.1155/2022/5780936
|View full text |Cite
|
Sign up to set email alerts
|

Study the Mechanism of Gualou Niubang Decoction in Treating Plasma Cell Mastitis Based on Network Pharmacology and Molecular Docking

Abstract: Objective. Explore the potential molecular mechanisms behind the therapeutic functions of Gualou Niubang decoction (GLNBD) in the treatment of plasma cell mastitis (PCM) by network pharmacology and molecular docking. Methods. GLNBD is a formula of Chinese traditional medicine consisting of 12 herbs. The potential active ingredients of GLNBD and their target genes were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform database, and PCM-related target genes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Researchers have studied these Chinese herbs and found that they contain active ingredients such as quercetin, luteolin, hesperetin, naringenin, and urushiol. [15][16][17] Quercetin is a dietary flavonoid that has effects on inflammation, angiogenesis, and vascular inflammation, it has anti-inflammatory, antioxidant, and antifungal properties, and can enhance the transcriptional activity of NRF2-ARE by inhibiting the NF-κB signaling pathway, therefore regulating the production of the inflammatory precursor NO. [15][16][17] Luteolin has a systemic anti-inflammatory effect and can regulate the TLR2 and TLR4 signaling pathways induced by S aureus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have studied these Chinese herbs and found that they contain active ingredients such as quercetin, luteolin, hesperetin, naringenin, and urushiol. [15][16][17] Quercetin is a dietary flavonoid that has effects on inflammation, angiogenesis, and vascular inflammation, it has anti-inflammatory, antioxidant, and antifungal properties, and can enhance the transcriptional activity of NRF2-ARE by inhibiting the NF-κB signaling pathway, therefore regulating the production of the inflammatory precursor NO. [15][16][17] Luteolin has a systemic anti-inflammatory effect and can regulate the TLR2 and TLR4 signaling pathways induced by S aureus.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Quercetin is a dietary flavonoid that has effects on inflammation, angiogenesis, and vascular inflammation, it has anti-inflammatory, antioxidant, and antifungal properties, and can enhance the transcriptional activity of NRF2-ARE by inhibiting the NF-κB signaling pathway, therefore regulating the production of the inflammatory precursor NO. [15][16][17] Luteolin has a systemic anti-inflammatory effect and can regulate the TLR2 and TLR4 signaling pathways induced by S aureus. Hesperetin can inhibit the activation of the NF-κB inflammatory pathway and control the occurrence of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we used the Gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis to evaluate the function and identify the pathways. The identified proteins were blasted against D. rerio , and the protein-protein interaction (PPI) networks were mapped using the Search Tool for the Retrieval of Interacting Genes/proteins (STRING) database ( 55 ). The pathway-enriched genes originated from the open-data resource of human pathways and reactions database, the Reactome ( 56 ).…”
Section: Methodsmentioning
confidence: 99%